2016
DOI: 10.21474/ijar01/2651
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness and Attitude of the Hazards of Carbon Monoxide (Co) Poisoning and the Safety Precautions Applied to That Regard, Among Saudis for the Year 2013-2014.

Abstract: Background:Carbon monoxide (CO) is a highly poisonous, odorless, colorless and non-irritating gas. It is formed by incomplete combustion of carbon or carbonaceous material. Because burning under conditions with insufficient oxygen will prevent complete oxidation to carbon dioxide (CO2), carbon monoxide gas will be formed. When inhaled, it will prevent absorption of oxygen by combining with hemoglobin in the blood, forming carboxyhemoglobin, which result in secondary tissue hypoxia and cellular damage, hence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
1
1
1
Order By: Relevance
“…Furthermore, an overwhelming majority of participants, accounting for 93.8%, indicated that their fuel burning devices underwent expert inspection at the onset of the winter season. In contrast to the findings reported by Hajjar et al (2016), it was seen that a majority (55.6%) of the individuals surveyed did not adhere to safety measures concerning carbon monoxide (CO). Furthermore, only a small percentage (1.7%) possessed a CO safety alarm.…”
Section: Prevention Practicescontrasting
confidence: 75%
“…Furthermore, an overwhelming majority of participants, accounting for 93.8%, indicated that their fuel burning devices underwent expert inspection at the onset of the winter season. In contrast to the findings reported by Hajjar et al (2016), it was seen that a majority (55.6%) of the individuals surveyed did not adhere to safety measures concerning carbon monoxide (CO). Furthermore, only a small percentage (1.7%) possessed a CO safety alarm.…”
Section: Prevention Practicescontrasting
confidence: 75%
“…According to their reports, (89.1%) of Iranis reported that CO detectors would be helpful for the decrease of mortality rates from CO poisoning, whereas (84.4%) reported that opening window is important prevention of CO leakage and (93.8%) indicated that, their fuel burning devices were checked by an expert at the beginning of the winter. In contrast to these reports (Hajjar et al, 2016) documented that more than half (55.6%) do not apply safety precautions related to CO, with only 1.7% owning a CO safety alarm resulting in a high prevalence of suffocation and death cases among the sample population (89.1%).…”
Section: Prevention Practicesmentioning
confidence: 80%
“…Gas ini terbentuk oleh pembakaran tidak sempurna karbon atau bahan berkarbon. Karena pembakaran dalam kondisi oksigen yang rendah sehingga terbentuk gas karbon dioksida (CO2) maka akan terbentuk gas CO. Bila dihirup akan mencegah penyerapan oksigen, gas CO akan bergabung dengan hemoglobin dalam darah membentuk karboksihemoglobin sehingga dinamakan "silent killer" (Hajjar et al, 2016). Sumber paparan gas monoksida diantaranya pembakaran industri, asap knalpot kendaraan, asap rokok, asap pembakaran dll.…”
Section: Hasil Dan Pembahasanunclassified